Fostering Religious Character Education Through the Implementation of Digital Literacy Culture - Eny Wahyu Suryanti; Any Ikawati (STAI Hubbulwathan Duri, 2025)
In the digital era, educators must adopt innovative strategies to integrate learning technology effectively. Digital literacy culture serves as a key approach to strengthening students' religious character education. This study explores strategies for enhancing religious character education through the implementation of digital literacy culture in schools. This research employs a qualitative descriptive approach, utilizing interviews, observations, and documentation for data collection. The study examines how digital literacy initiatives contribute to character development within the school environment. Findings indicate that the integration of digital literacy culture in religious character education is facilitated through various literacy programs, character-building activities, and technology-based innovation movements. These initiatives not only improve students' engagement with digital tools but also reinforce essential moral values. The implementation of digital literacy culture significantly enhances the quality of innovative learning while fostering core religious values such as honesty, discipline, skills, independence, responsibility, and tolerance. These attributes prepare students to navigate the challenges of the globalized world. The study concludes that digital literacy culture is an effective strategy for strengthening religious character education. Future research should explore broader educational settings and assess long-term impacts to further optimize digital literacy initiatives in character development.